2009
DOI: 10.1167/iovs.09-3694
|View full text |Cite
|
Sign up to set email alerts
|

Common Sequence Variation in theVEGFAGene Predicts Risk of Diabetic Retinopathy

Abstract: Sequence variation in the VEGFA gene is associated with risk of developing blinding DR in T1DM and T2DM. Identifying specific genetic markers will allow for refined screening algorithms and earlier intervention in patients at highest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 50 publications
0
62
0
Order By: Relevance
“…The study selection process is shown in figure 1. A total of 9 studies examined the association between the VEGF -2578C/A polymorphism and DR [13,14,15,16,17,18,19,20,21]. Of these, 3 studies for which the data was unavailable were excluded [19,20,21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study selection process is shown in figure 1. A total of 9 studies examined the association between the VEGF -2578C/A polymorphism and DR [13,14,15,16,17,18,19,20,21]. Of these, 3 studies for which the data was unavailable were excluded [19,20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 3 studies for which the data was unavailable were excluded [19,20,21]. Thus, 6 studies were included in the current meta-analysis [13,14,15,16,17,18]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF is believed to play a significant role in the development of diabetic complications. VEGFA variants were associated with the development of diabetic retinopathy [46,47] . Ginsenoside Rb1 obviously enhanced the expression of VEGF and enhanced myocardial angiogenesis [48] .…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have investigated the associations between polymorphisms in the VEGFA gene and DR. -634G/C (+405G/C or rs2010963) polymorphism in the 5′-untranslated region and-2578C/A (−2549I/D (in high linkage disequilibrium with -2578C/A) or rs699947) polymorphism in the promoter region of the VEGFA gene are most frequently investigated. However, the results have been inconsistent [5][6][7][8][9][10][11][12][13][14][15][16]. To date, three relevant meta-analyses [17][18][19] have published.…”
Section: Introductionmentioning
confidence: 99%